Закономерности деформационного поведения и акустической эмиссии в сплаве АМГ6 - Макаров С. В. Сергей Викторович; Лысиков М. В. Михаил Валерьевич; Колубаев Е. А. Евгений Александрович; Плотников В. А. Владимир Александрович (2015, 2015)
Заглавие с экрана